The Soloist [videorecording] - Wright, Joe 1972-.; Foxx, Jamie (Hollywood, CA Dreamworks Home Entertainment, 2009)
Los Angeles Times reporter Steve Lopez discovers Nathaniel Anthony Ayers, a former classical music prodigy, playing his violin on the street of L.A. A unique friendship is formed, one that transforms both their lives.
VCD
Based on the book "The soloist : a lost dream, an unlikely friendship, and the redemptive power of music" by Steve Lopez.
Originally released as a motion picture in 2009.
Jamie Foxx, Robert Downey, Jr., Catherine Keener, Tom Hollander, Lisa Gay Hamilton.
Keywords: Journalists -- Drama; Cellists -- Drama; African American homeless persons -- California -- Los Angeles -- Drama; Schizophrenics -- Drama; Mentally ill homeless persons -- Drama; Music -- Drama